KURSUS BIMBINGAN BELAJAR GRATIS DI SD NEGERI 094134 TIGAURUNG PAMATANG SIDAMANIK - Marbun, Yanty Maria Rosmauli; Tarida Simanjuntak; Adhe Novtriandani Damanik; Dahlia Fortuna Sinaga; Sabna Marchhayuni Girsang; Fery Christian S. Turnip; Frans Nico A. Lumbantoruan (Universitas PGRI Adi Buana Surabaya, 2022)
This community service activity aims to be able to improve the ability of students to study mathematics, Indonesian and civic education and English during the current pandemic. In this case, the free guidance course in question is learning that is carried out outside school hours and is free of charge from students. With community service activities (PKM) carried out in each Faculty, it is a program that really helps the community with things like today. Where students participate in helping to educate the nation's life. Moreover, especially in the selection of community service locations (PKM), students are required to be smarter and more literate with educational problems that occur at community service locations (PKM). From the teaching system, it appears that the condition of the school is good in teaching its students. But again, the problem of technology seems to need to be introduced and used when teaching in the classroom. With the help of these media can provide renewal for students that make them enthusiastic, active, and interested in the learning process.